Odpowiedzi

Najlepsza Odpowiedź!
2009-09-13T20:10:26+02:00

a) 0,5x + y = 2
0,5x + y = -2

y = 2 - 0,5x
0.5x+( 2 - 0.5x))=-2

y = 2 - 0,5x
0.5x+2-0.5x=-2

y = 2 - 0,5x
0x=-4



b) -2x + y = 2
6x - 3y = -6

y= 2 + 2x
6x - 3(2+2x)=-6

y= 2 + 2x
6x-6-6x=-6

y= 2 + 2x
0x=0
2009-09-13T22:49:46+02:00
0.5x +y = 2
0.5x +y = -2
z pierwszego y=2 - 0.5x
0.5x + 2 - 0.5x = -2
2 jest różne od -2 wiec uklad numer 1 nie ma rozwiązania


-2x + y = 2 y = 2+2x
6x - 3y = -6
6x - 3(2+2x) = -6
6x -6 - 6x = -6
-6 = -6

a wiec uklad ten ma nieskończenie wiele rozwiązań